THE EXCHANGE OF CONNECTIVE TISSUE BIOPOLYMERS IN THE LIVER OF ALLOXAN DIABETIC RATS - S. V. Lomaeva; I. F. Gette; T. S. Bulavintseva; S. E. Perevedentseva; I. G. Danilova (Бюллетень сибирской медицины)
Aim. Study of the exchange of liver and blood plasma biopolymers of alloxan diabetic rats.Materials and Methods. Diabetes mellitus was modeled in rats by single subcutaneous injection of alloxan tetrahydrate (170 mg per100 gbody weight). Blood glucose, glycosylated hemoglobin were controlled and morphometric study of the pancreas was carried out for the verification of the model. A month later, concentration of glycosaminoglycans, free hydroxyproline and the level of hyaluronidase and collagenolytic activity in plasma were determined. The total concentration of collagen, glycosaminoglycans, and their fractions, the level of hyaluronidase and collagenolytic activity in rat liver homogenate were measured.Results. The level of all the parameters of interest in the liver and blood plasma increased on 30 day after alloxan injection, the accumulation of glycosaminoglycans in the liver occurred mainly due to unsulfonated fraction.Conclusion. The development of experimental diabetes in rats is accompanied by activation of both decay processes and synthesis of biopolymers studied. Accumulation of total collagen and glycosaminoglycans was observed in rats’ liver, which probably lead to the fibrosis changes in it.